2023
DOI: 10.1111/sms.14330
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fatigue during maximal eccentric‐only, concentric‐only, and eccentric‐concentric bicep curl exercise with automated drop setting

Abstract: Connected adaptive resistance exercise (CARE) machines are new technology purported to adjust resistance exercise loads in response to muscle fatigue. The present study examined muscle fatigue (strength loss, fatigue perceptions) during maximal eccentric‐only (ECCmax‐only), concentric‐only (CONmax‐only), and coupled ECC‐CON (ECCmax‐CONmax) bicep curl exercise on a CARE machine. Eleven men and nine women completed the three protocols in separate sessions and in random order. All protocols included 4 sets of 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…15 We identified relevant studies using a mixed approach similar to that described by Greenhalgh and Peacock. 17 This approach relied on the investigators' personal knowledge and checking of personal digital files associated with previous research, 5,6,18,19 keyword searches performed in PubMed and Google Scholar (e.g., "eccentric" AND "concentric" AND "fatigue"), and "snowballing" strategies (i.e., reference and citation tracking). Articles were eligible for inclusion in the review if they included human subjects and reported muscle strength data (e.g., torques, forces) before and at the end of acute bouts of ECC max , CON max , or coupled ECC max -CON max resistance exercise.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…15 We identified relevant studies using a mixed approach similar to that described by Greenhalgh and Peacock. 17 This approach relied on the investigators' personal knowledge and checking of personal digital files associated with previous research, 5,6,18,19 keyword searches performed in PubMed and Google Scholar (e.g., "eccentric" AND "concentric" AND "fatigue"), and "snowballing" strategies (i.e., reference and citation tracking). Articles were eligible for inclusion in the review if they included human subjects and reported muscle strength data (e.g., torques, forces) before and at the end of acute bouts of ECC max , CON max , or coupled ECC max -CON max resistance exercise.…”
Section: Methodsmentioning
confidence: 99%
“…In one study, participants exercised with maximal effort on a connected adaptive resistance exercise machine, which involved maximal muscle actions performed within a range of velocities and with an external resistance that decreased (i.e., drop setting) in real-time to match the participant's force-generating capacity with fatigue. 5 The ECC max and CON max exercise protocols typically involved a prescribed number of sets and repetitions. The protocols ranged from 1 to 10 sets (3.4 ± 2.5 sets) and from 6 to 100 muscle actions per set (29.3 ± 28.5 repetitions).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This drop setting feature, first described elsewhere [33], enabled the individual to perform the greatest possible number of repetitions on the machine without need to disengage from it, and this occurred for both the accentuated eccentric and eccentric-only exercise. Two recent experiments [59,60] have confirmed the automated eccentric overload and drop set features of the machine and also validated the machine's load in different ways: (a) strong correlations (r ≥ 0.94) were found between maximal concentric phase strength on the machine and a one repetition maximum test with a dumbbell; (b) agonist muscle activity during maximal effort repetitions on the machine was equal to or greater than during a one repetition maximum test with a dumbbell; and (c) during fatiguing exercise on the machine, heightened perceptions of fatigue occurred in concert with strength loss. Data in Fig.…”
Section: Care In the Laboratorymentioning
confidence: 98%
“…Here, our purpose is to illustrate the potential of CARE technology to deliver accentuated eccentric and eccentriconly resistance exercise rather than to discuss the particular advantages and disadvantages of each machine. To illustrate the potential of CARE technology for delivering eccentric resistance exercise, we describe one CARE machine (Trainer + , Vitruvian, West Perth, Australia) We describe this machine because it is the one we are most familiar with [33,59,60] and because it exhibits most features of eccentric exercise technologies recommended by Tinwala and colleagues [19]. For example, the machine has distinct modes for accentuated eccentric and eccentriconly exercise, permits multiple degrees of freedom, has an easy-to-use interface via its mobile phone application, and provides real-time performance feedback and options for downloading and sharing results.…”
Section: Care Overviewmentioning
confidence: 99%